The Reflection of Nasimi`S Concepts in The Works of Atoi - Kadirovna, Amonova Zilola; Shavkatovna, Sharipova Mekhriniso (International Journal of Psychosocial Rehabilitation, 2020)
In the mysticism literature of the East, various controversial ideas about Nasimi and his ideas are widespread. The stories about Imamiddin Nasimi are widely given in the works of Atoi, Lutfi, Gadoi, Sakkoki, Latifi. In addition,  many  poets  were  inspired  by  the  ideas  of  Imamiddin  Nasimi  and  quoted  his  name and ideas in their poems. In particular, this situation is reflected in the work of Atoi. The article analyzes Atoi`s wisdom about Imamiddin Nasimi and his ideas of the mysticism sect. It is worth mentioning that the Sufi poet also mentioned the name of Imamiddin Nasimi in his works related to the Qur`an and expressed his views. In covering this issue, attention is paid to Nasimi`s contribution to the development of the genre of mysticism, his unique style and artistic skills, unlike other poets. The study used analytical and comparative methods.